Inovasi Pelayanan Perizinan Berusaha Terintegrasi Secara Elektronik atau Online Single Submission (OSS) Bagi UMKM di Kota Tangerang - Putri, Aulia Anggita; Rahmawati, Rahmawati (ANTASENA: Governance and Innovation Journal, 2024)
This research aims to identify and analyze innovations in electronically integrated business licensing services or Online Single Submission (OSS) for MSMEs in Tangerang City. This research is motivated by the fact that there are still many MSMEs in Tangerang City that have not registered their business licenses or do not have a Business Identification Number (NIB). There are still many business actors or MSMEs who do not understand the service procedures for applying for business licenses through the Online Single Submission (OSS) system. The method used in this research is descriptive qualitative with data obtained through observation, interviews, and documentation. OSS innovation in business licensing is seen through relative advantage, suitability, complexity, observability, and trialability. In its implementation, business licensing through OSS has run well in relative advantage, suitability, and observability. In the Complexity dimension, there are still some business actors or MSMEs who have difficulty understanding this system even though various socializations have been carried out. In addition, in the Triability dimension, OSS innovations have not carried out public trials at the regional level and have not involved innovation users in the implementation of innovation trials.